Flexibility Provisions in Multilateral Environmental Treaties - Bernhard Boockmann; Paul W. Thurner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
In international politics, intergovernmental treaties provide the rules of the game. Similar to private law, treaty designers face a trade-off between flexibility to adjust to unforeseen contingencies and the danger that the binding nature of the treaty and hence, the level of commitment by treaty members, is being undermined if the treaty can be amended too easily. In this paper, we address this problem in the analytical framework of institutional economics, drawing in particular on the incomplete contracts literature. Furthermore, we derive preliminary hypotheses and operational concepts for the measurement of flexibility in international treaties. Based on 400 treaties and supplementary agreements from the field of international environmental law, we provide new insights into the combined application of rules for adoption and entry into force of amendments, as well as provisions for conflict resolution and interpretative development. Using correspondence analysis, we show that treaty provisions can be represented in a two-dimensional property space, where treaties can be arrayed according to the degree of institutionalisation as well as along a flexibility dimension.
Keywords: 330; Umweltabkommen; Umweltrecht; international; Flexibilität; Unvollständiger Vertrag; Welt